Kiai, Pesantren, and Educational Leadership in Madura: The Genealogy of Religious Authority within Local Power Structures - Bukhari, Ach Baidlawi; Hasan, Nor; Syarif, Zainuddin; Solichin, Mohammad Muchlis (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study aims to examine the genealogy of kiai authority in Madura and to analyze how such authority is sustained through pesantren institutions and subsequently transformed into educational governance and local political leadership. Employing a qualitative library research design with a conceptual and interpretive analytical approach, data were systematically collected from Scopus, Web of Science, Google Scholar, Dimensions, and Crossref databases. Relevant publications were selected through a rigorous screening procedure based on thematic relevance, academic credibility, duplication, publication period, and conceptual contribution. The selected sources were subjected to analytical coding, thematic categorization, comparative synthesis, and critical interpretation through the integrative lens of Weber’s theory of authority, Gramsci’s theory of hegemony, and contemporary Islamic educational leadership perspectives. The findings reveal that kiai authority in Madura is genealogically rooted in pesantren traditions, personal charisma, religious knowledge, santri networks, community trust, and local cultural values. Pesantren function not merely as institutions for Islamic knowledge transmission but as comprehensive centers of educational leadership, character formation, moral socialization, and authority reproduction. The authority of kiai further extends into local politics through moral legitimacy, social mobilization, cultural influence, and the mediation of relations between society and political elites. This study implies that pesantren-based leadership offers a significant model of value-based educational governance that can strengthen character education, ethical leadership, social cohesion, and community-oriented development in contemporary Islamic education.